Bending Properties of Short-Cut Basalt Fiber Shotcrete in Deep Soft Rock Roadway - Shaoyang Yan; Huazhe Jiao; Xiaolin Yang; Jinxing Wang; Fengbin Chen (Advances in Civil Engineering, 2020)
To study the effect of short-cut basalt fiber (BF) on the bending and toughening properties of shotcrete, bending toughness tests of short-cut BF shotcrete slabs with different volume fractions were carried out. A transparent soil model and Scanning Electron Microscopy (SEM) were used to observe the distribution of BF with different volume fractions and analyze the toughness enhancement mechanism of basalt fiber shotcrete. The supporting effect of basalt fiber shotcrete with different volume fractions was verified by an underground engineering test. The test results show the following: (1) when the fiber content is within 3∼4.5 kg/m3, the distribution of BF in transparent soil is uniform, and it does not easily agglomerate, which is beneficial to improving the bending toughness of shotcrete. (2) The shotcrete slab with 4.5 kg/m3 fiber content had the best reinforcing effect. Compared with the control group, the peak load and absorption capacity increased by 56.67% and 636.96%, respectively, and the maximum crack width decreased by 32.10%. (3) The SEM analysis indicated that the basalt fibers distributed randomly and evenly in the concrete, which can form a three-dimensional spatial skeleton with a stable structure. Excessive fiber incorporation can increase fiber agglomeration during stirring and spraying. (4) The support results of an underground engineering test show that, in 35 days, short-cut basalt fiber shotcrete with 4.5 kg/m3 fiber content is better at restraining the surrounding rock than shotcrete with other fiber contents. BF has the properties of crack resistance, bridging, and toughening for shotcrete and can significantly improve the ability of shotcrete to restrain surrounding rock deformation. As a new type of fiber, BF has great significance in deep soft rock underground engineering.